Synthesis of Few-Layer GaSe Nanosheets for High Performance Photodetectors - Hu, PingAn; Wen, Zhenzhong; Wang, Lifeng; Tan, Pingheng; Xiao, Kai (ACS nano, 2012)
Two-dimensional (2D) semiconductor nanomaterials hold great promises for future electronics and optics. In this paper, a 2D nanosheets of ultrathin GaSe has been prepared by using mechanical cleavage and solvent exfoliation method. Single- and few-layer GaSe nanosheets are exfoliated on an SiO2/Si substrate and characterized by atomic force microscopy and Raman spectroscopy. Ultrathin GaSe-based photodetector shows a fast response of 0.02 s, high responsivity of 2.8 AW–1 and high external quantum efficiency of 1367% at 254 nm, indicating that the two-dimensional nanostructure of GaSe is a new promising material for high performance photodetectors.